A Cross Sectional Study on the Prevalence of Elder Abuse in the Rural Field Pracrtice Areas of A Tertiary Care Hospital In Mangaluru - Narayana, Venkatesh Krishna; Suresh, Sucharitha; R, Chandrashekar (Journal of Pharmacy Practice and Community Medicine)
Objectives: The objectives of this study was to define and identify the symptoms of elder abuse, create awareness about its existence to the primary health care workers and recommend an appropriate strategy for its prevention. Methods: A descriptive cross-sectional study by questionnaires based was done considering prevalence and problems of elder abuse in Dakshina Kannada rural areas of Jaranadagudde and Ammunje district, peripheral health centres, Mangaluru, Karnataka, India in February, 2016. Results: The study showed that the prevalence of abuse was 1.57% in the sample population and undoubtedly, the offenders were their children even though it is quite low comparatively. Conclusion: Even though low, we opine that, to prevent elder abuse, interventions and policies are of utmost importance and help reduce the burden on the ageing population especially in a developing country like India.
Keywords: Burden; Cross-sectional Study; Elder abuse; Prevalence; Problems; Survey